2007
DOI: 10.1074/jbc.m609485200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Arginine Methylation on RBP16 mRNA Binding, Guide RNA (gRNA) Binding, and gRNA-containing Ribonucleoprotein Complex (gRNP) Formation

Abstract: Mitochondrial gene expression in Trypanosoma bruceiinvolves the coordination of multiple events including polycistronic transcript cleavage, polyadenylation, RNA stability, and RNA editing. Arg methylation of RNA binding proteins has the potential to influence many of these processes via regulation of protein-protein and protein-RNA interactions. Here we demonstrate that Arg methylation differentially regulates the RNA binding capacity and macromolecular interactions of the mitochondrial gene regulatory protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…RNA editing initiates with formation of the gRNA/pre-mRNA hybrid, prior to pre-mRNA cleavage. Evidence from in vitro RNA editing assays indicates that RBP16 stimulates editing at, or prior to, the cleavage of pre-mRNA (Miller et al 2006), and RBP16 interacts with both gRNA and mRNA in vivo (Hayman and Read 1999;Goulah and Read 2007). In this paper, we have demonstrated that RBP16 has RNA annealing and unwinding activity.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…RNA editing initiates with formation of the gRNA/pre-mRNA hybrid, prior to pre-mRNA cleavage. Evidence from in vitro RNA editing assays indicates that RBP16 stimulates editing at, or prior to, the cleavage of pre-mRNA (Miller et al 2006), and RBP16 interacts with both gRNA and mRNA in vivo (Hayman and Read 1999;Goulah and Read 2007). In this paper, we have demonstrated that RBP16 has RNA annealing and unwinding activity.…”
Section: Discussionmentioning
confidence: 61%
“…In addition to its in vivo association with gRNAs, it has been shown to associate with 9S and 12S rRNAs and a subset of mRNAs in T. brucei mitochondria (Hayman and Read 1999;Militello et al 2000;Goulah and Read 2007). RBP16 was the first characterized RNA editing accessory factor, and both in vivo and in vitro assays demonstrate a role for RBP16 in stimulation of RNA editing (Pelletier and Read 2003;Miller et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, arginine methylation was shown to decrease the capacity of RBP16 to associate with gRNA. This is not a general effect on RBP16 RNA binding, however, since methylation conversely increases the association of the protein with mRNA (Goulah and Read 2007). In the case of SFPQ/PSF, it is clear that arginine methylation increases its association with mRNA.…”
Section: Discussionmentioning
confidence: 95%
“…For glycerol gradient analysis, mitochondrial lysates from PF strain 29-13 (equivalent to 5 ϫ 10 9 cells) were purified as indicated previously (23). Mitochondrial vesicles were lysed in lysis buffer (25 mM Tris (pH 8.0), 50 mM KCl, 10 mM MgOAc, 0.2% Nonidet P-40) for 5 min on ice.…”
Section: Cloning and Expression Of Tbrgg2-thementioning
confidence: 99%